Associations between eHealth literacy, mental health-seeking attitude, and mental wellbeing among young electronic media users in China during the COVID-19 pandemic - Xu, Richard Huan; Bao, Xiao-lu; Shi, Lu-shao-bo; Wang, Dong (Frontiers in Public Health, 2023)
Objective This study aimed to examine the associations among mental health related eHealth literacy (eHL), mental health-seeking attitude, and well-being among Chinese young electronic media users during the COVID-19 pandemic. Methods A web-based cross-sectional survey was conducted in Guangzhou, China. The modified eHealth literacy Scale, Mental Help-Seeking Attitudes Scale, and Short Warwick-Edinburgh Mental Well-being Scale were used. Structural equation modeling (SEM) examined the associations between them and was adjusted by several controlled variables. Results Totally, 1,008 participants completed the questionnaire and provided valid responses. The eHL showed a statistically significant and direct effect on mental well-being in this sample. The higher the level of eHL, the better well-being of the participants. The mental health-seeking attitude is also positively correlated with mental well-being, indicating that the more positive attitude toward seeking mental health services, the better the well-being participants reported. The higher level of eHL is significantly associated with a more positive attitude toward seeking mental health services. Conclusion Training to improve eHL may optimize young electronic media users’ mental health outcomes. Development and use of a mental health specific eHL instrument in future studies should be encouraged.